Prognostic Value of Preoperative Hemoglobin Levels for Long-Term Outcomes of Acute Type B Aortic Dissection Post-thoracic Endovascular Aortic Repair - Gao, Zhichun; Qin, Zhexue; An, Zhixia; Hou, Changchun; Wang, Luyu; Jin, Jun (Frontiers in Cardiovascular Medicine, 2020)
Background and aims There is scant information available about the prognostic value of preoperative hemoglobin (Hb) levels on the long-term outcomes of acute type B aortic dissection (ABAD) following thoracic endovascular aortic repair (TEVAR). Methods A retrospective analysis of consecutive patients from 2010 to 2018 regarding the relationship between Hb level and long-term outcomes was conducted. The primary endpoint was all-cause mortality. Major adverse cardiovascular events (MACEs) included all-cause death, recurrent ruptures and secondary procedures. Results In total, 391 subjects treated by TEVAR were enrolled, with a mean age of 57.1±12.0 years; 79.5% of them were male. Cox multivariate analysis showed that the preoperative Hb level was independently associated with all-cause death [adjusted hazard ratio (HR) 0.797(per 1 g/dL), 95% confidence interval (CI) 0.693-0.918, p=0.002] and MACEs (adjusted HR 0.795, 95%CI 0.672-0.871, p=0.000). The area under the receiver operating characteristic curve of Hb for all-cause death and MACEs were 0.617 (95%CI 0.548-0.687, p=0.008) and 0.617 (95%CI 0.551-0.684, p=0.005), respectively. In the linear trend test, Hb concentration was significantly related to all-cause mortality (p for trend=0.001) and MACEs (p for trend=0.000). Moreover, in Kaplan-Meier analysis, lower Hb levels (< 12 g/dL) were significantly different from higher Hb (≥12 g/dL) levels for both all-cause death (log-rank p=0.001) and MACEs (log-rank p=0.001). Similar results were found when assessing the prognostic value of red blood cell count and anemia. Conclusions Preoperative Hb may serve as a prognostic marker for long-range adverse outcomes for ABAD patients post-TEVAR.